Raise the Cigarette Tax, [LULAC letters to Rep. Moran and the Washington Post regarding excise taxes] (Tufts Archival Research Center, 2007)
Letters from League of United Latin American Citizens (LULAC) opposing increases in excise taxes. Thanks Rep. Dan Rostenkowski for rejecting higher excise taxes. Accuses excise taxes of being discriminatory, undemocratic, and impermanent. Criticizes the Washington Post for endorsing an increase in the cigarette tax. Predicts that a tax increase would be ineffective at reducing the smoking rate.